Computed tomographic coronary angiography in risk stratification prior to non-cardiac surgery: a systematic review and meta-analysis. Issue 17 (24th April 2019) - Koshy, Anoop N; Ha, Francis Jonathan; Gow, Paul J; Han, Hui-Chen; Amirul-Islam, FM; Lim, Han S; Teh, Andrew W; Farouque, Omar
Abstract : Objectives: Utility of CT coronary angiography (CTA) and coronary artery calcium (CAC) scoring in risk stratification prior to non-cardiac surgery is unclear. Although current guidelines recommend stress testing in intermediate-high risk individuals, over one-third of perioperative major adverse cardiovascular events (MACE) occur in patients with a negative study. This systematic review and meta-analysis evaluates the value of CTA and CAC score in preoperative risk prognostication prior to non-cardiac surgery. Methods: MEDLINE, PubMed and EMBASE databases were searched for articles published up to June 2018. Summary ORs for degree of coronary artery disease (CAD) and perioperative MACE were pooled using a random-effects model. Results: Eleven studies were included. Two hundred and fifty-two (7.2%) MACE occurred in 3480 patients. Risk of perioperative MACE rose with the severity and extent of CAD on CTA (no CAD 2.0%; non-obstructive 4.1%; obstructive single-vessel 7.1%; obstructive multivessel 23.1%, p<0.001). Multivessel disease (MVD) demonstrated the greatest risk (OR 8.9, 95% CI 5.1 to 15.3, p<0.001). Increasing CAC score was associated with higher perioperative MACE (CAC score: ≥100 OR 5.1, ≥1000 OR 10.4, both p<0.01). In a cohort deemed high risk by established clinical indices, absence of MVD on CTA demonstrated a negative predictive value of 96% (95% CI 92.8 to 98.4) for predicting freedom from MACE. Conclusions: Severity and extent of CAD on CTA conferred incremental risk for perioperative MACE in patients undergoing non-cardiac surgery. The 'rule-out' capability of CTA is comparable to other non-invasive imaging modalities and offers a viable alternative for risk stratification of patients undergoing non-cardiac surgery. Trial registration number: CRD42018100883